The SiD Digital ECal Based on Monolithic Active Pixel Sensors - Brau James E.; Breidenbach Martin; Dragone Angelo; Habib Alexandre; Rota Lorenzo; Vassilev Mirella; Vernieri Caterina (EPJ Web of Conferences)
Higgs physics goals with detectors at future colliders demand unprecedented precision. Linear colliders, with energy reach to the TeV scale and low duty cycles and backgrounds, enable this high precision performance. The SiD Collaboration is developing Monolithic Active Pixel Sensor (MAPS) technology for tracking and electromagnetic calorimetry (ECal). This technology offers high granularity, thin sensors, good time resolution (<nsec), and small dead areas, enabled by gaseous cooling for tracking and passive thermal conduction for calorimetry. The first MAPS prototype (NAPA-p1), designed by SLAC in CMOS imaging 65 nm technology, is under test. The long-term objective is a wafer-scale sensor of area 5 × 20 cm2. Detailed simulation of ECal performance confirms previous results, indicating electromagnetic energy resolution based on digital hit cluster counting provides better performance than the 13 mm2 pixels SiD TDR analog design, and two particle separation in the ECal is excellent down to the millimeter scale. Recent heat management analysis indicates passive cooling for the low duty cycle linear colliders should work.